LABA USAHA KOPERASI: DAMPAK PERPUTARAN MODAL KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) OBOR KOTA BIMA TAHUN 2015-2019 - Mursyid, Fadilah Try (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
The aim of this research is to analyze Cooperative Business Profit: Impact of Capital Turnover of the Koperasi Pegawai Republik Indonesia (KPRI) Obor Kota Bima Tahun 2015-2019. The research is quantitative research with the primary data source being documentation data about business capital turnover, and secondary data from interviews with cooperative administrators. The data analysis technique used is cooperative ratio analysis using the capital turnover ratio analysis formula. The research results show that this year's net sales achievement has decreased drastically from 2015-2019. Development of business capital The amount of business capital has increased. The amount of business capital that has increased has also increased in terms of assets or wealth owned. From the aspect of effectiveness and efficiency, it is very effective because it can be seen from the profit generated from sales from year to year which has increased. Profitability analysis increases every year. The Koperasi Pegawai Republik Indonesia (KPRI) Obor Kota Bima should be able to maintain its working capital efficiently, and the cooperative's management system should be able to improve its liquidity to prevent funds from remaining idle in the cash which will affect the amount of profit generated from decreasing.